Basal ganglia intensity indices and diffusion weighted imaging in manganese-exposed welders. Issue 6 (23rd March 2012) - Criswell, Susan R; Perlmutter, Joel S; Huang, John L; Golchin, Nima; Flores, Hubert P; Hobson, Angela; Aschner, Michael; Erikson, Keith M; Checkoway, Harvey; Racette, Brad A
Abstract : Objectives: Manganese exposure leads to diffuse cerebral metal deposition with the highest concentration in the globus pallidus associated with increased T1-weighted MRI signal. T1 signal intensity in extra-pallidal basal ganglia (caudate and putamen) has not been studied in occupationally exposed workers. Diffusion weighted imaging is a non-invasive measure of neuronal damage and may provide a quantification of neurotoxicity associated with welding and manganese exposure. This study investigated extra-pallidal T1 basal ganglia signal intensity as a marker of manganese exposure and basal ganglia diffusion weighted imaging abnormalities as a potential marker of neurotoxicity. Methods: A 3T MR case:control imaging study was performed on 18 welders and 18 age- and gender-matched controls. Basal ganglia regions of interest were identified for each subject. T1-weighted intensity indices and apparent diffusion coefficients were generated for each region. Results: All regional indices were higher in welders than controls (p≤0.05). Combined basal ganglia (ρ=0.610), caudate (ρ=0.645), anterior (ρ=0.595) and posterior putamen (ρ=0.511) indices were more correlated with exposure than pallidal (ρ=0.484) index. Welder apparent diffusion coefficient values were lower than controls for globus pallidus (p=0.03) and anterior putamen (p=0.004). Conclusions: Welders demonstrated elevated T1 indices throughout the basal ganglia. Combined basal ganglia, caudate and putamen indices were more correlated with exposure than pallidal index suggesting more inclusive basal ganglia sampling results in better exposure markers. Elevated indices were associated with diffusion weighted abnormalities in the pallidum and anterior putamen suggesting neurotoxicity in these regions.